Implementasi Pembelajaran Berdiferensiasi Berbasis Kurikulum Merdeka pada Mata Pelajaran PAI - Aulia Mawaddah, Ida; Khairunnisa, Dira (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to describe the implementation of differentiated learning based on the independent curriculum in Islamic Religious Education (PAI) subjects at SMKN 3 Sumbawa Besar. The research method used is descriptive qualitative with data collection techniques through observation and interviews. The results of the study indicate that the implementation of differentiated learning based on the independent curriculum in PAI subjects at SMKN 3 Sumbawa is carried out by considering differences in students' interests, talents, and abilities. Teachers use various learning strategies. Learning materials are presented by integrating spiritual and moral values in everyday life. Assessments are carried out authentically by considering cognitive, affective, and psychomotor aspects. The results of the implementation show an increase in student motivation, participation, and learning achievement in PAI subjects. It can be concluded that the implementation of differentiated learning based on the independent curriculum in PAI subjects at SMKN 3 Sumbawa Besar is running well and has a positive impact on student development.